Designing and using innovative learning spaces: What teachers have to say - Julia Morris; Wesley Imms (IUL Research)
As many schools are moving towards more innovative learning environments, there is an ongoing need for evidence about how teachers and students use these innovative spaces to enhance learning. While innovative learning environments have been characterised as spaces that are more flexible, with ubiquitous technology and the ability to reconfigure space dependent on the learning task, there is no universal definition of what constitutes a truly ‘innovative’ learning environment because each school context is unique. Consequently, how innovative learning environment designs are used in practice will vary depending on the needs of students, teachers and school communities. The Plans to Pedagogy project, developed by the University of Melbourne’s Learning Environments Applied Research Network (LEaRN) team, is exploring the educational issues school leaders and teachers identify as they transition to and use innovative learning environments. It acknowledges that no two schools are the same, and each school has unique spatial challenges. Plans to Pedagogy, embedded in a range primary and secondary schools across Australia and New Zealand, has eight current projects. Each school is assigned a LEaRN academic who works with a small teaching team to co-design and implement a research project targeting the school’s identified spatial challenge. The eight current projects focus on issues such as promoting student agency and developing 21st century learning skills in students, mapping collaborative teaching practices, assessing the impact of furniture on student engagement, and supporting the transition of teachers’ pedagogy as they move from traditional to innovative environments. As each has a unique focus, the research methods used differ case to case. However, a common principle is that each case needs to build evidence that is disseminated to the school community, with the aim of sharing learning to support teachers’ and students’ praxis in innovative learning environments.